Impact of COVID-19 vaccinations on UK stock market - Chengyue Lu; Wojtek Paczos (Cardiff University, Cardiff Business School, 2024)
Using London Stock Exchange data (Jan 10, 2021, to Feb 24, 2022) and fixed-effects regression methods, this study assesses COVID-19 vaccine effects on UK stock returns. Initial protocol doses have a strong positive impact on returns, while boosters have a modest positive impact. A logarithmic unit increase in daily vaccine doses links to a 0.085p.p. stock return increase. Stringent closure policies weaken the positive vaccine influence on returns. Sector-wise, healthcare responds most positively, while basic resources and food/beverage industries show a positive but muted effect. This study sheds light on the contribution of Covid-19 vaccinations on economic recovery in the UK.
Keywords: E65; G12; I18; 330; stock returns; Covid-19; vaccinations